Breast cancer metastases in central nervous system. Case report and review of literature - I. Radzevičiūtė; R. Pačinskaitė; R. Gleiznienė (Neurologijos seminarai)
Breast cancer is the most frequently diagnosed cancer among women worldwide. The most common first site of distant spread is bone, followed by lung, brain, and liver. Symptoms of meta- static breast cancer can vary greatly depending on the location of the metastases. Symptoms of metastases of breast cancer in the brain, depending on location, can include nausea, headache, hemiparesis, blurred vision, seizures, slurred speech, impaired thinking, dizziness. Breast carcinoma tends to metastasize to the cerebellum and the basal ganglia. A very aggressive intraventricular, leptomeningeal spread to the central nervous system is also possible; however, it is a rare localization of breast cancer metastasis. Magnetic resonance imaging (MRI) is the most sensitive diagnostic tool for the detection of brain metastases. Treatment approaches of brain metastases include surgery, stereotactic radiosurgery (SRS), and whole brain radiation therapy (WBRT). In this article we present a case of a 34-year-old woman with a clinical diagnosis of breast cancer and metastases to the central nervous system. The patient received treatment at the stereotactic radiosurgery centre Sigulda in Latvia; during the course of the disease, intraventricular metastatic spread to the brain was diagnosed. In addition, the article also reviews the literature on the clinical presentation of intracerebral breast cancer metastases, diagnosis, and treatment recommendations.